Searching of Pregnancy Rate in Repeat Breeder Cows by Embryo Transfer Practices - Hakan Sağırkaya; Erkan Say (Journal of Agricultural Sciences)
The aim of this study is to compare the pregnancy rates by applying embryo transfer to the cows which are not pregnant and should be removed from herd as repeat breeder. In this study, 87 randomlyselected Holstein cows utilized. The repeat breeder cows (n=45) were selected from at least one giving birth, having regular sexual cycle, missing clinical worsening into genital organ and not displaying anabnormal discharge. On the other hand, it was selected from nonpregnant cows which inseminated artificially at least 3 times or more. Besides, cows that used as the control group (n=42) were selected fromthe cows without any artificial insemination postnatally. The PGF2α application was performed to all recipient cows which are considered to benefit from as a recipient in control and testing groups just 24 daysbefore the flushing day. After this application, the cows showing estrous symptoms were recorded and determined as candidate recipients. The pregnancy rates were 35.6% and 50% for testing and control groups, respectively and the difference between the groups was significant (P<0,05). As a result, even this difference between the groups it has been concluded that embryo transfer can be used to conceive especially for high-yielding cows as a treatment method for repeat breeder cows. Thereby, embryo transfer from the cows with high superior characteristics to the high milk yielding cows which have infertilityproblems can economically be beneficial by utilizing the high milk yield in the later lactation without any replacement cost.